2003
DOI: 10.1128/iai.71.4.1820-1827.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Anti-HelicobacterpyloriImmunity following Systemic Immunization of Neonatal Mice

Abstract: Helicobacter pylori infection of the gastric mucosa is a significant cause of morbidity and mortality because of its etiologic role in symptomatic gastritis, peptic ulcer disease, and gastric adenocarcinoma. Infection occurs in young children; therefore, a prophylactic vaccine would have to be administered within the first year of life, a period thought to be immunologically privileged. We investigated vaccine formulations administered by different routes to confer protective anti-H. pylori immunity in neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
2
24
1
2
Order By: Relevance
“…28,30 Perhaps most surprising has been the observation that protective immunity equivalent to orogastric delivery can be induced through the use of systemic routes, including subcutaneous and intraperitoneal. [32][33][34] These results are in contrast to the failure of systemic immunization to protect against other mucosal pathogens but have been the impetus for at least 1 phase 3 clinical trial using parenteral immunization described later. 35 Second, protection in mice can be achieved using numerous distinct H pylori protein antigens.…”
Section: Results From the Mouse Model That Contributed To Vaccine Devcontrasting
confidence: 65%
See 1 more Smart Citation
“…28,30 Perhaps most surprising has been the observation that protective immunity equivalent to orogastric delivery can be induced through the use of systemic routes, including subcutaneous and intraperitoneal. [32][33][34] These results are in contrast to the failure of systemic immunization to protect against other mucosal pathogens but have been the impetus for at least 1 phase 3 clinical trial using parenteral immunization described later. 35 Second, protection in mice can be achieved using numerous distinct H pylori protein antigens.…”
Section: Results From the Mouse Model That Contributed To Vaccine Devcontrasting
confidence: 65%
“…49 Lastly, prophylactic immunization against H pylori is effective when administered to neonatal mice. 32 This experiment has important implications if a vaccine is to be administered to humans at an early age. Although there may be utility in administering a therapeutic vaccine to the adult population in countries where H pylori-associated gastric cancer remains prevalent, a more effective strategy for long-term reductions in H pylori infections and associated pathology may be to immunize children because most infections occur in early childhood.…”
Section: Results From the Mouse Model That Contributed To Vaccine Devmentioning
confidence: 99%
“…Gottweln et al reported that the two kinds of H pylori vaccine with complete Freund's or aluminum as adjuvant, which induce Th1 and Th2 immune response respectively, could induce protective immune response in vivo in mice, indicating that Th1 and Th2 immune response have the effect of immune protection. Eisenberg et al [21] immunized neonatal and adult mice with H pylori antigen and complete or incomplete Freund's adjuvant and found that the number of T cells producing Th1 cytokines like IFN-γ, IL-2 and Th2 cytokines like IL-4 IL-5 increased, have the effect of immune protection. Sommer et al [22] used CpG oligonucleotide as adjuvant to induce Th1 immune response, and found that it could not protect against H pylori infection but lead to more serious gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have shown shown that TGF-β acts inhibited the secretion of pro-inflammatory cytokines: Th1 and Th17. "Knockout" mice for TGF-β develop a deadly generalized inflammation (50). Study has demonstrated that the naïve CD4+ T cell development into Treg was enhanced in the presence of GECs (Gastric Epithelial Cells) derived TGF-β.…”
Section: Role Of Regulatory T Cells In Thementioning
confidence: 99%